Peran Guru Dalam Pembentukan Karakter Peserta Didik di SDIT Al-Mizan Rengasdengklok - Anjani, Ulpah Tri; Mas'shum, Sya'roni; Lubis, Saprialman (El-Idare, 2023)
This research aims to determine the role of teachers in shaping students' character education. This study used a qualitative approach with a descriptive research type while the data collection technique in this study used the interview method. Dhuha prayer, memorizing short verses, Asmaul Husna, the attributes of Allah, and tahlil together every Friday. In addition, the teachers make habits for students. For example, by making a habit of reading prayers before and after lessons start and end. The character building through the example of the teacher is done with the teacher by giving advice related to character education during the morning assembly, the learning process, and students' daily activities at school. The character formation of students at SDIT Al-Mizan Rengasdengklok must continue to be carried out to achieve student output that can contribute to character education. Character formation is not only the responsibility of schools and teachers, but the role of parents in supervising and forming character in the family environment is very necessary. By strengthening the formation of student character in the family environment, it will be easier for schools to shape it so that later students become role models in schools, communities, nations and countries.